Scleral imbrication with vitreoretinal surgery as a primary procedure for retinal detachment in pathological myopia - Gitanjli Sood; Sandeep Mahajan (Indian Journal of Ophthalmology)
A 45-year-old male presented with diminution of vision in the right eye (RE) for the past 2 weeks. He underwent sequential bilateral cataract surgery 25 years ago, with an intraocular lens in RE, which was his better eye. The left eye was aphakic with a thick fibrous membrane at the pupillary plane. Visual acuity was hand movement in the RE with the iris claw lens and total bullous retinal detachment (RD). The axial length with RD was 28.6 mm in RE and 29 mm in the left eye (LE). We did a vitrectomy with scleral imbrication, endolaser, fluid gas exchange, and tamponade in the RE. The LE developed RD subsequently, and he underwent similar surgical procedures in his LE. The best corrected visual acuity in his RE was 20/80, and that in the LE was 20/120 on follow-up. RD with staphyloma is a surgical challenge as the thin atrophic retina at the posterior pole fails to conform to the concavity of staphyloma. Vitrectomy with tamponade alone does not take care of staphyloma and has more chances of recurrent detachment or persistent fluid at the posterior pole. Scleral imbrication shallows the staphyloma cavity and shortens the axial length, thereby giving a good surgical outcome.